Deacetylation of furanosides using banana as biocatalyst - Taverna Porro, Marisa Lia (2007)
The deacylation under hydrolytic conditions of methyl 2,3,5-tri-O-acetyl-α-d-ribofuranoside, methyl 2,3,5-tri-O-acetyl-β-d-ribofuranoside, methyl 2,3,5-tri-O-acetyl-α,β-d-arabinofuranosides and alkyl 2,3,5-tri-O-acetyl-α,β-xylofuranosides have been studied using banana whole tissue as biocatalyst. Reaction regioselectivity strongly depends on substrate structure. Hydrolysis of methyl 2,3,5-tri-O-acetyl-α-d-ribofuranoside afforded methyl 2,3-di-O-acetyl-α-d-ribofuranoside in quantitative yield.